2018
DOI: 10.1007/s11356-018-2923-0
|View full text |Cite
|
Sign up to set email alerts
|

Factors that control the spatial and temporal distributions of phosphorus, nitrogen, and carbon in the sediments of a tropical reservoir

Abstract: The impacts of anthropic activities have had profound effects on the nitrogen (N) and phosphorus (P) cycles in many aquatic ecosystems. We investigated the spatial and temporal distributions of carbon (C), N, and P in the sediments of a tropical Paiva Castro Reservoir (São Paulo, Brazil), as well as their release and retention in the system. In 2010, surface sediments were collected at nine sites in the reservoir, and a core was obtained in the limnetic zone, in 2010. The core was dated using the Pb technique.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 54 publications
2
6
0
Order By: Relevance
“…The link between LULC and EC pore-water values is consistent with other studies that reported positive correlations between this parameter and intensive agriculture activities and urban classes [7,52]. Further, streams surficial sediments were characterized as inorganic, with mean percentages of organic matter (OM) contents less than 6 [53]. Table 1.…”
Section: Physico-chemical Parameterssupporting
confidence: 88%
“…The link between LULC and EC pore-water values is consistent with other studies that reported positive correlations between this parameter and intensive agriculture activities and urban classes [7,52]. Further, streams surficial sediments were characterized as inorganic, with mean percentages of organic matter (OM) contents less than 6 [53]. Table 1.…”
Section: Physico-chemical Parameterssupporting
confidence: 88%
“…In fact, the depth of the water at the sediment sampling location described the vast majority (84.1%) of the variation in looselybound P and over half of the variation (63.1%) in total P concentrations. The pattern of higher concentrations at greater depths is likely driven by sediment focusing and greater net sediment deposition in deeper portions of the lake (White & Stone, 1996;Hou et al, 2014;Cardoso-Silva et al, 2018). The direct relationship that we observed between water depth and sediment P concentrations is consistent with other studies of spatial variation in sediment P pools (Nowlin et A factor that may influence the spatial distribution of the sediment P pool is the location and density of macrophyte beds.…”
Section: Intra-lake Variation In Sediment P Poolssupporting
confidence: 90%
“…The spatial distribution of the sediment P pool is also heterogeneous within individual shallow lakes following variation in sediment transport, deposition, and resuspension processes (Mackay et al, 2012). Sediment total P generally increases with water depth as a result of sediment focusing, which concentrates fine-grained, P-enriched sediments in deeper portions of the lake basin (White & Stone, 1996;Hou et al, 2014;Cardoso-Silva et al, 2018). Dynamic disturbance and biological activity across the lakebed further drive spatial variation in sediment P speciation in shallow waterbodies (Forsberg, 1989;Nowlin et al, 2005;Kowalczewska-Madura et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…Surface sediments of the Alqueva reservoir are mainly inorganic, with OM contents < 12% [67]. Despite the high variability of TPs concentrations, much influenced by oxic conditions, pH and iron forms [68], all the sediments presented concentrations of TPs higher than the severe effect level (TP SEL > 0.2%; [69]), classifying the sediments as heavily polluted, and likely to affect the health of sediment-dwelling organisms. Montante was the location with the highest concentrations of TP s , achieving values of 17.5% in the wet period for both years.…”
Section: Chemical Patternsmentioning
confidence: 99%